Causes of permanent vertical deformation at subduction margins: Evidence from late Pleistocene marine terraces of the southern Hikurangi margin, Aotearoa New Zealand - Ninis, Dee; Howell, Andy; Little, Timothy; Litchfield, Nicola (Frontiers in Earth Science, 2023)
Studies of the seismic cycle at convergent margins anticipate that coseismic deformation is recovered, yet permanent vertical displacement of the overriding plate is observed at many subduction margins. To understand the mechanisms driving permanent vertical displacement, we investigate uplift across the southern Hikurangi margin, Aotearoa New Zealand, in the last ~200 ka. Marine terraces preserved along the Wellington coast have previously been dated as MIS 5a, 5c, 5e and 7a in age. We use these ages with reconstructions of paleo-strandline elevations, to calculate uplift rates across the margin and to examine the processes responsible for their elevation. The highest uplift rate – 1.7 ± 0.1 mm/yr – and maximum tilting – 2.9º to the west – are observed near Cape Palliser, closest to (~40 km from) the Hikurangi trough. Uplift decreases monotonically westward along the Palliser Bay coast, to 0.2 ± 0.1 mm/yr at Wharekauhau (~70 km from the trough), defining a west-tilted subaerial forearc. Locally, active oblique-slip upper-plate faults cause obvious vertical offsets of the marine terraces in the axial ranges (>70 km from the trough). Uplift rates at Baring Head, on the upthrown side of the Wairarapa Fault, are ~0.7-1.6 mm/yr. At Tongue Point, uplift on the upthrown side of the Ōhāriu Fault is 0.6 ± 0.1 mm/yr. Dislocation modelling constrained by these uplift rates indicate that deep-seated processes – the earthquake cycle on the subduction interface, the buoyancy of the subducting Hikurangi Plateau, and sediment underplating – contribute ≤0.4 mm/yr to permanent vertical displacement across the margin. By contrast, slip on faults within the overriding Australian Plate dominates the ≳1 mm/yr of uplift at Cape Palliser and Baring Head and are responsible for >20% (and probably >50%) of permanent uplift; depending on their geometry and slip rate, such faults could be responsible for ≥80% of Late Pleistocene uplift above the southern Hikurangi Margin. These results indicate a significant contribution of slip on upper-plate faults to permanent uplift across the subduction margin. They indicate that in regions where upper-plate faults are prevalent, strong constraints on fault geometry and activity are necessary to determine contributions of deeper-seated uplift processes.